Quality measurement in fitness centers in Salgueiro/PE - Italo César Felipe SILVA; Fagner José Coutinho de Melo; Eryka Fernanda Miranda SOBRAL; Bartira Pereira AMORIM; Claudia Editt Tornero BECERRA; Tiago Silveira MACHADO (Universidade Estadual de Alagoas, 2023)
The objective of this paper was to evaluate the quality of services provided by fitness centers in the municipality of Salgueiro, using the SERVQUAL model, developed to measure the quality of services, through the differences between perceptions and expectations that customers have of the service provided. Additionally, the QUESC scale was used, which is a method specifically designed to measure the quality of the fitness service. The research is classified as an applied type with a quantitative approach. The use of SERVQUAL and the integrated QUESC method are shown to be of great value for quality management in gyms that use this tool, the results obtained were analyzed via descriptive statistics. Among the main results of the research, the dimensions with priority that deserve more attention stand out, such as: tangibility (Attribute 30: the gym must innovate programs in order to encourage clients to practice exercises), credibility (Attribute 10: Instructors must always be willing to help their clients and Attribute 31: The gym must have accident safety measures and emergency procedures in place) and empathy (Attribute 33: The gym must have secure parking for clients, Attribute 5: Clear instructions and reliable and Attribute 8: Employees and instructors must be involved and committed to the quality and improvement of services provided). In this way, the study contributes to theory (scientifically), as it discusses research that has not yet been carried out in the municipality and in practice (socially), it can be used so that managers of these gyms can introduce corrective actions for possible problems. found, pointing out and understanding its main limitations and issues inherent to the satisfaction of people who attend and enjoy its services, offering strategic and theoretical knowledge to its managers.